1962
DOI: 10.1002/pol.1962.1206217406
|View full text |Cite
|
Sign up to set email alerts
|

Structural dependence of the electrical conductivity of polyethylene terephthalate

Abstract: The direct current conductivity of three different forms of polyethylene terephthalate was studied over a wide temperature and voltage range to determine the structural dependence of the conduction process. From the films in the amorphous, crystallized, and oriented and crystallized forms it was determined that crystallization reduces the conductivity by more than one order of magnitude. Orientation results in a sixfold decrease in conductivity. The conductivity does not change over a wide range of molecular w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…The experimental points in both directions locate approximately between two straight lines, the dashed line drawn through the origin (m= I) and the solid line drawn through the point of 1.9 times as the origin (m= 1.9), with slope of I. Therefore it can be concluded that (3) for Cell I. The result also supports the hopping conduction mechanism in cellulose.…”
Section: •-10supporting
confidence: 69%
See 1 more Smart Citation
“…The experimental points in both directions locate approximately between two straight lines, the dashed line drawn through the origin (m= I) and the solid line drawn through the point of 1.9 times as the origin (m= 1.9), with slope of I. Therefore it can be concluded that (3) for Cell I. The result also supports the hopping conduction mechanism in cellulose.…”
Section: •-10supporting
confidence: 69%
“…respectively, where e is a protonic charge. The calculated values of 11 and nat 140-230°C are 10-12 m 2 /V s and 10 22 m- 3 . These values Polymer J., Vol.…”
Section: •-10mentioning
confidence: 84%
“…Therefore, this should shift the occurrence of the thermal runaway or the electronic avalanche towards higher electric fields. For instance, Amborski has carried out that crystallization results in the conductivity decrease in poly(ethylene terephthalate), 12 interfaces and a hopping jump distance reduction (i.e., increase in the trap density) in the bulk when polypropylene crystallinity rises. 13 In previous papers, we reported the influence of a thermal annealing of PA-HT leading to a strong reduction of the charge carrier mobility and/or density 14 and of the dynamics of the local and segmental chain motions in the amorphous phase.…”
Section: Introductionmentioning
confidence: 99%
“…The former values also seem to be lower than those for other insulating polymer materials such as amorphous polyethylene terephthalate (10-l2 S/m at 100"C). 9 Activation energies for electric conductivity were obtained for silicone rubbers and gels from Arrhenius plots and ranged from 42 to 60 kJ/mol. Our activation energies are remarkably low compared to those of such wellknown insulating polymers as polyester and epoxide resin which have been reported to be 142 kJ/mol at 30-90"C10 and 214 kJ/mol at 100-130"C,1 respectively.…”
Section: Methodsmentioning
confidence: 99%